Automatic interpretation and writing report of the adult waking electroencephalogram - Shibasaki, Hiroshi; Nakamura, Masatoshi; Sugi, Takenao; Nishida, Shigeto; Nagamine, Takashi; Ikeda, Akio (Clinical neurophysiology, 2014)
•A computer-assisted system for automatic, systematic and comprehensive interpretation of the adult waking EEG was developed for the first time.•This new system can provide a written report of the adult waking EEG which is in good conformity with the results of visual inspection of the same record by qualified electroencephalographers (EEGers).•This system can be applied to the clinical diagnosis of EEG as a supplementary tool to the EEGer’s visual inspection and to the education of EEG trainees and EEG technicians. Automatic interpretation of the EEG has so far been faced with significant difficulties because of a large amount of spatial as well as temporal information contained in the EEG, continuous fluctuation of the background activity depending on changes in the subject’s vigilance and attention level, the occurrence of paroxysmal activities such as spikes and spike-and-slow-waves, contamination of the EEG with a variety of artefacts and the use of different recording electrodes and montages. Therefore, previous attempts of automatic EEG interpretation have been focussed only on a specific EEG feature such as paroxysmal abnormalities, delta waves, sleep stages and artefact detection. As a result of a long-standing cooperation between clinical neurophysiologists and system engineers, we report for the first time on a comprehensive, computer-assisted, automatic interpretation of the adult waking EEG. This system analyses the background activity, intermittent abnormalities, artefacts and the level of vigilance and attention of the subject, and automatically presents its report in written form. Besides, it also detects paroxysmal abnormalities and evaluates the effects of intermittent photic stimulation and hyperventilation on the EEG. This system of automatic EEG interpretation was formed by adopting the strategy that the qualified EEGers employ for the systematic visual inspection. This system can be used as a supplementary tool for the EEGer’s visual inspection, and for educating EEG trainees and EEG technicians.